Performance of solar photocatalysis and photo-fenton degradation of palm oil mill effluent [Prestasi fotopemangkinan dan degradasi foto-fenton menggunakan sinar suria ke atas efluen kilang minyak kelapa sawit] - Devagi, Kanakaraju; Nurul Liyana, Ahmad; Noorfaezah, Mohd Sedik; Long, Sylvester Gan Hsien; Tay Meng, Guan; Lim, Ying-Chin (The Malaysian Analytical Sciences Society, 2017)
Palm oil mill effluent (POME) contains significant amounts of organic matter, solids, and grease or oil, which requires appropriate treatment prior to being discharged into the environment. In this study, solar radiation was investigated as a possible source of photon in the solar TiO2 and ZnO photocatalysis, and solar photo-Fenton treatments to reduce the chemical oxygen demand (COD) in POME. The results indicated that solar photo-Fenton was more efficient in reducing COD levels compared to dark Fenton and indoor photo-Fenton. The highest removal was recorded at 89% in the presence of 1:30 ratio of Fe2+:H2O2 under acidic pH (~2.8) after 3 hours of solar exposure. Increased concentrations of H2O2 have greatly influenced the COD removal. Additionally, solar TiO2 photocatalysis (pH~3.7; TiO2 = 0.1 g/L) has outperformed solar photolysis and solar ZnO photocatalysis in reducing COD levels in POME. With successive increase of TiO2 from 0.02 to 0.1 g/L, the removal of COD had linearly increased from 54.3% to 88.5% after 5 hours of solar exposure. Based on the investigated conditions, the optimum TiO2 concentration of 0.1 g/L was concluded. In conclusion, solar TiO2 photocatalysis and solar photo-Fenton can be applied as possible means to reduce the organic loads in POME. © 2017, Malaysian Society of Analytical Sciences. All rights reserved.